Non-Invasive Stent Removal after Ureteroneocystostomy in Pediatric Patients: Long-Term Results - Issi, Yasar (Urology Journal, 2020)
Objective: Among the more serious problems in urological interventions among the pediatric age group is the requirement of general anesthesia. The advantages of removing a double-J stent (DJS) without anesthesia in ureteroneocystostomy (UNC) operations among children were investigated in this study. Patients and Methods: In all, 25 patients who underwent UNC surgery between November 2016 and November 2018 were retrospectively divided into two groups according to the method used for the removal of the DJS. In Group 1, the stent was tied to the urethral catheter by a suture and retrieved postoperatively on the fourth day without anesthesia and cystoscopy. In Group 2, we inserted the stent according to the classical method with no suturing to the catheter and removed it 3 to 4 weeks after the first operation, with cystoscopy under anesthesia. Results: A total of 16 girls and 9 boys were included in the study. The mean age was 4.3 and 6.3 years in groups 1 and 2, respectively. We did not observe statistically significant difference between the groups in long-term renal function or hydronephrosis regression. Conclusion: We consider that the removal of a stent placed in pediatric intravesical UNC operations without anesthesia and cystoscopy is less invasive and affords safety and long-term results comparable to the standard method.